Krakowski Judenrat - Zajączkowska-Drożdż, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article deals with the history of Jews in Kraków during the German occupation. After discussing the origins and essence of the Judenrat as an institution, the author presents its legal determinants as well as the history of the Kraków Judenrat established by a decision of the Nazi occupation authorities. The author’s contention is that the Kraków Judenrat evolved from an institution focused on helping the local Jewish community into an institution blindly following the German orders, and that the change was associated with a change of people responsible for this policy.
Keywords: Holokaust; antysemityzm; Judenrat; Kraków